A Supramolecular Substance, [2] Rotaxane, Induces Apoptosis in Human Molt-3 Acute Lymphoblastic Leukemia Cells - Kimura, M.; Makio, K.; Hara, K.; Hiruma, W.; Fujita, Y.; Takata, T.; Nishio, K.; Ono, N. (Drug Research, 2015)
The antitumor effects of a supramolecular substance, the [2] rotaxane (TRO-A0001), and its molecular mechanisms were investigated. TRO-A0001 suppressed the proliferation of cultured human Molt-3 acute lymphoblastic leukemia cells for 12–72 h in a dose-dependent manner. Based on flow cytometry, TRO-A0001 clearly induced apoptosis after 24 h. The mitochondrial membrane potential disappeared after treatment with 1.0 µM of TRO-A0001. Expression of the cleaved forms of capase-9 and caspase-3 was significantly increased in cells exposed to TRO-A0001, whereas the expression of XIAP, a type of inhibitor of apoptosis family, was decreased. These results suggest that [2] rotaxane TRO-A0001 may be a highly promising new antitumor medicine.